Guidelines for Robot-to-Human Handshake From the Movement Nuances in Human-to-Human Handshake - Cabibihan, John-John; El-Noamany, Ahmed; Ahmed, Abdelrahman Mohamed Ragab M.; Ang, Marcelo H. (Frontiers in Robotics and AI, 2022)
The handshake is the most acceptable gesture of greeting in many cultures throughout many centuries. To date, robotic arms are not capable of fully replicating this typical human gesture. Using multiple sensors that detect contact forces and displacements, we characterized the movements that occured during handshakes. A typical human-to-human handshake took around 3.63 (+/-0.45) s to perform. It can be divided into three phases: reaching (0.92+/-$0.10 s), contact (1.96+/-0.46 s), and return (0.75+/-0.12 s). The handshake was further investigated to understand its subtle movements. Using a multiphase jerk minimization model, a smooth human-to-human handshake can be modelled with fifth or fourth degree polynomials at the reaching and return phases, and a sinusoidal function with exponential decay at the contact phase. We show that the contact phase (1.96 s) can be further divided according to the following subphases: preshake (0.06 s), main shake (1.31 s), postshake (0.06 s), and a period of no movement (0.52 s) just before both hands are retracted. We compared these to the existing handshake models that were proposed for physical human-robot interaction (pHRI). From our findings in human-to-human handshakes, we proposed guidelines for a more natural handshake movement between humanoid robots and their human partners.